Seismic reflection methods in offshore groundwater research - Bertoni, C; Lofi, J; Micallef, A; Moe, H (MDPI, 2020)
There is growing evidence that passive margin sediments in offshore settings host large volumes of fresh and brackish water of meteoric origin in submarine sub-surface reservoirs. Marine geophysical methods, in particular seismic reflection data, can help characterize offshore hydrogeological systems and yet the existing global database of industrial basin wide surveys remains untapped in this context. In this paper we highlight the importance of these data in groundwater exploration, by reviewing existing studies that apply physical stratigraphy and morpho-structural interpretation techniques to provide important information on—reservoir (aquifer) properties and architecture, permeability barriers, paleo-continental environments, sea-level changes and shift of coastal facies through time and conduits for water flow. We then evaluate the scientific and applied relevance of such methodology within a holistic workflow for offshore groundwater research.